THE INTERNET OF THINGS (IOT) REVOLUTION IN CONNECTED EDUCATION: INFRASTRUCTURE, PRIVACY, AND INCLUSION CHALLENGES IN BRAZIL - de Abreu, Felipe Menezes; Quaresma, Elias Ramos; Silva, Emerson Leandro da Silva; Santos, Glaucia Nunes de Lima; das Chagas, Maria Joselia Mendes; da Silva, Paulo Adriano Maciel; de Jesus, Paulo Cristiano Abreu (Seven Editora, 2026)
This article analyzes the impact of the Internet of Things (IoT) on school management and pedagogical practices in Brazil. Through a bibliographic and documentary review of national sources published between 2020 and 2025, it investigates how the interconnection of physical objects (sensors, wearables, and smart devices) can transform the school environment into "Smart Schools" ecosystems. The Brazilian regulatory landscape is discussed concurrently, with emphasis on the General Data Protection Law (LGPD) and the National Connected Schools Strategy, addressing the risks of excessive surveillance, the data security of minors, and the infrastructure disparity between public and private networks. DOI: https://doi.org/10.56238/sevened2026.001-015